2010
DOI: 10.1055/s-0030-1251915
|View full text |Cite
|
Sign up to set email alerts
|

Lebensbedrohliche Komplikationen von Morbus Crohn und Colitis ulcerosa

Abstract: Complications of both IBD and immunosuppressive therapy may be live-threatening in patients with IBD. Better characterization of patients with a high probability of improved outcome by immunosuppressive and/or antibody-therapy seems to be preferable to noncritical early use of these drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…9 Huber et al reported on 28 patients admitted to a German university hospital ICU between 1991 and 2008 and found a case-fatality rate of 18%, of which all deaths were all attributed to infectious complications. 10 This study was published in German and only the English language abstract was reviewed. Most…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…9 Huber et al reported on 28 patients admitted to a German university hospital ICU between 1991 and 2008 and found a case-fatality rate of 18%, of which all deaths were all attributed to infectious complications. 10 This study was published in German and only the English language abstract was reviewed. Most…”
Section: Discussionmentioning
confidence: 99%
“…The cohort of patients we describe in this study represents approximately one-fourth of the overall total reported in the literature we identified. 9,10,12 Additionally, similar to the studies from Manitoba, we used a population-based design that minimises selection bias and allows reporting of incidence and mortality rates. 23 This is an important consideration, as while single hospital-based studies may inform clinical experience, they are at particular risk for referral bias.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations